2003
DOI: 10.1111/j.1471-0528.2003.02395.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of total compared with subtotal hysterectomy with one‐year follow up results

Abstract: A smaller proportion of women suffered from urinary incontinence after total abdominal hysterectomy than after subtotal abdominal hysterectomy one year post-operatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(50 citation statements)
references
References 55 publications
5
45
0
Order By: Relevance
“…Eleven studies were identified (8–18). Details of study design, indications for hysterectomy, types of surgery and pain data are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies were identified (8–18). Details of study design, indications for hysterectomy, types of surgery and pain data are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Women in the SA group recovered faster. In previous studies concerning abdominal hysterectomy and quality of life, the measurements were conducted a minimum of 4 weeks postoperatively and do not reflect the immediate postoperative period (1–3,26,27). Improvements in HRQoL were found in these studies, similar to our results, but we also found a remaining difference in the mental components of the HRQoL 6 months after the operation, favoring women in the SA group.…”
Section: Discussionmentioning
confidence: 99%
“…7,[12][13][14][15][16][17][18][19] However, comparative studies consisting of a patient control group who under-went a different operation in the same time-span as the hysterectomy group found no detrimental effect after TAH compared with the control group at up to 2 years of follow up. 5,[20][21][22][23][24][25] This difference in reported UI rates may be explained by the follow-up intervals as the potential anatomical alteration of the bladder and neurological damage may result in progressive damage years after a TAH. [26][27][28][29] The long-term follow up of our study has demonstrated that statistically more women were referred with UI after a TAH than after a TCRE (15 versus 7%).…”
Section: Discussionmentioning
confidence: 99%